2020
DOI: 10.1002/jlb.1mr0520-221rr
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of DOCK family proteins on T and B cells

Abstract: The dedicator of cytokinesis (DOCK) family proteins consist of 11 members, each of which contains 2 domains, DOCK homology region (DHR)-1 and DHR-2, and as guanine nucleotide exchange factors, they mediate activation of small GTPases. Both DOCK2 and DOCK8 deficiencies in humans can cause severe combined immunodeficiency, but they have different characteristics. DOCK8 defect mainly causes high IgE, allergic disease, refractory skin virus infection, and increased incidence of malignant tumor, whereas DOCK2 defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 120 publications
(238 reference statements)
0
9
0
2
Order By: Relevance
“…Numerous studies have taken TP53 as a marker gene of ferroptosis. DOCK2 encodes the dedicator of cytokinesis 2 protein, which is mainly expressed in peripheral blood immune-related cells and is involved in changes of cytoskeleton proteins when chemokines act on lymphocytes [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have taken TP53 as a marker gene of ferroptosis. DOCK2 encodes the dedicator of cytokinesis 2 protein, which is mainly expressed in peripheral blood immune-related cells and is involved in changes of cytoskeleton proteins when chemokines act on lymphocytes [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The encoded protein is a member of the DOCK family of Rho GTPase activators and may have a role in activating T cells 33 and the development of CD8+ T cells. 34 DOCK10 is also differentially downregulated in contact dermatitis when presented with sensitizers. 35 Our data suggests that genetic variation may modify risk of developing ASM-induced SJS/TEN via perturbation of DOCK10 activity in HLA-B*15:02-positive individuals.…”
Section: Discussionmentioning
confidence: 97%
“…The suggestive variants identified in the HLA ‐ B*15 : 02 ‐positive subanalysis might affect splicing of the DOCK10 gene. The encoded protein is a member of the DOCK family of Rho GTPase activators and may have a role in activating T cells 33 and the development of CD8+ T cells 34 . DOCK10 is also differentially downregulated in contact dermatitis when presented with sensitizers 35 .…”
Section: Discussionmentioning
confidence: 99%
“…One set of circRNAs originated from genes that have been implicated in neuronal development, synaptic plasticity, and neuronal survival. It was interesting to see a rise in circRNAs derived from the DOCK1 locus, which encodes a member (DOCK1, also known as DOCK180) of a family of 11 'dedicator of cytokinesis' proteins implicated in activating small GTPases [44]. Although it is widely expressed, in the neural tube, DOCK1 was shown to participate in the axonal outgrowth elicited by the protein netrin and implicating the signaling protein RAC1 [45].…”
Section: Discussionmentioning
confidence: 99%
“…Expression of only a subset of circRNAs (red box in Figure 8A) is linked to the abundance of its linear RNA counterpart whereas another subset of circRNAs (blue box in Figure 8A) appears to be present summarizes circRNAs differentially abundant in brain samples from AD relative to normal individuals, produced from parent RNAs that were transcribed from gene loci linked to AD pathology. The gene names ('Gene'), relative levels and significance for circRNAs displaying the greatest differences in abundance ('logFC', 'p-value'), number of studies in which the circRNAs were found differentially abundant ('# Studies'), the circRNAs more abundant (up) and less abundant (down) in AD relative to normal, the genomic location ('Coordinates'), and the 'Relation to Alzheimer's Disease', and the pertinent references are indicated [44][45][46][47][48][49][50][51][52].…”
Section: Linear Vs Circrna Expression In Ad Samplesmentioning
confidence: 99%